The experiences of endometriosis patients with diagnosis and treatment in New Zealand - Katherine Ellis; Deborah Munro; Deborah Munro; Rachael Wood; Rachael Wood (Frontiers Media S.A., 2022)
Endometriosis is a chronically painful, invasive, inflammatory disease, with limited treatment options and long delays to diagnosis, which impacts 10% of females in New Zealand.IntroductionAs part of a larger group discussion study, this paper covers three themes associated with endometriosis patient experiences: intensity of pain, diagnostic tool shortcomings and perspectives of treatment options.Materials and methodsThe goal of this research was the inclusion of patient voices to guide research priorities. In early 2022, 50 New Zealand endometriosis patients participated in anonymous, asynchronous, text-based group discussions on the VisionsLive platform. The patients ranged in age from 18-48. The patients answered 50 questions, 23 text-based and 27 quantitative, and then took part in online group discussions.Results and discussionThe average age of symptom onset was 15.3 years, while the average delay from symptom onset to a working or surgically confirmed diagnosis was 7.91 years. The top five reported symptoms within the cohort were pain-based, and the participants discussed the many impacts of this pain on their work and education. The four main diagnostic tools employed on this cohort were abdominal ultrasound (72%), transvaginal ultrasound (68%), laparoscopy (82%) and sharing their symptom history with a medical practitioner (88%). The most common emotions patients experienced following receiving a diagnosis of endometriosis were relief (86%), feeling overwhelmed (54%), and anger (32%). The main treatments offered to this cohort were pain relief (96%), laparoscopic surgery (84%) and the combined oral contraceptive pill (80%). Of these three treatments, only laparoscopic surgery was viewed positively by the majority of users, with 67% considering laparoscopy an effective treatment, compared to 46% of users for pain relief, and 25% of users for the combined oral contraceptive pill.ConclusionsGathering the voice of patients revealed that long delays to diagnosis and dismissal by medical practitioners frequently manifests as a reaction of relief by patients once diagnosed. Results also showed treatment options such as pain relief and hormonal medications were often considered ineffective, but were routinely offered as the first, or only, options for patients. It is therefore important that both quicker routes to diagnosis and more effective treatment options be developed.